Óbidos, literary village: innovation in the creative industries? - Centeno, Maria João (2016)
Artigo baseado na comunicação proferida na 7th Annual Research Session: ENCATC: Cultural Management Education in Risk Societies: Towards a Paradigm and Policy Shift?!, realizado na Universitat de Valencia, Valencia, Espanha, 05-07 outubro 2016